2020
DOI: 10.1097/sla.0000000000003768
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repair of Blunt Thoracic Aortic Trauma is Associated With Increased Left Ventricular Mass, Hypertension, and Off-target Aortic Remodeling

Abstract: Background: Aortic elasticity creates a cushion that protects the heart from pressure injury, and a recoil that helps perfuse the coronary arteries. TEVAR has become first-line therapy for many aortic pathologies including trauma, but stent-grafts stiffen the aorta and likely increase LV afterload. Objective: Test the hypothesis that trauma TEVAR is associated with LV mass increase and adverse off-target aortic remodeling. Methods: Computed Tomography Angiography (CTA) scans of 20 trauma TEVAR patients (17 M/3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…56 After endovascular stent implantation, increases in pulse wave velocity have been measured, along with concurrent increases in left ventricular hydraulic load (which is similar characteristic impedance), left ventricular hypertrophy, diastolic dysfunction, and potentially detrimental effects on coronary perfusion, although the clinical ramifications have not been fully delineated. [57][58][59] The surrounding aortic tissue may also be impacted. After ascending aortic replacement with an interposition graft, greater aortic strain has been measured in the native descending aorta, suggesting that a larger pulse wave (and possibly greater loading or shearing forces) is being transmitted.…”
Section: Aortic Interposition Grafts and Thoracic Stentingmentioning
confidence: 99%
“…56 After endovascular stent implantation, increases in pulse wave velocity have been measured, along with concurrent increases in left ventricular hydraulic load (which is similar characteristic impedance), left ventricular hypertrophy, diastolic dysfunction, and potentially detrimental effects on coronary perfusion, although the clinical ramifications have not been fully delineated. [57][58][59] The surrounding aortic tissue may also be impacted. After ascending aortic replacement with an interposition graft, greater aortic strain has been measured in the native descending aorta, suggesting that a larger pulse wave (and possibly greater loading or shearing forces) is being transmitted.…”
Section: Aortic Interposition Grafts and Thoracic Stentingmentioning
confidence: 99%
“…We found that few of these studies clearly distinguished RAS from RAI. Postoperative acute kidney injury (AKI) and refractory hypertension are common complications and severely impact the prognosis after TEVAR (9,10). Renal artery stenosis but not RAI could be one of the reasons for these complications.…”
Section: Introductionmentioning
confidence: 99%
“…The same process, but faster and worse, happens after open or endovascular aortic grafting operations, leading to an increased cardiac afterload and onset of arterial hypertension. 2,3 Consequently, the left ventricle remodels with an augmented mass, and the coronary system, especially if already reduced in its reserve and then decreased in its blood supply, dissection, but are possible consequences to be evaluated at the moment of surgical decision. Furthermore, the basal principle also remains valid that the length of the aortic prosthesis must respect the safety limits in its proximal and distal anchoring levels, in order to incorporate the most diseased aortic tract and reduce risks of secondary endoleaks, mainly of type 1b.…”
mentioning
confidence: 99%